Adequacy of physician clinical rounds and nursing care elements for non-COVID-19 infected patients admitted during the COVID-19 pandemic - Abdullah Alrasheed; Jinan Shamou; Rajkumar Rajendram; Abdulaziz Boqaeid; Salman Qasim; Waleed Baharoon; Laila layqah; Salim Baharoon (Elsevier, 2022)
Background: The COVID-19 pandemic created many challenges for healthcare systems. Frontline workers and especially healthcare professionals were the most severely affected through increased working hours, burnout and major psychological distress. Objectives: To evaluate the changes in standard care elements which occurred during the COVID-19 pandemic, specifically the physician clinical rounds and nursing care provided to non-COVID-19 infected patients. Design: Observational retrospective study. Settings: The study was conducted at King Abdulaziz Medical City, Riyadh Saudi Arabia. KAMC is a 1200 bed tertiary care referral academic medical center. Patients (materials) and methods: We compared the physician clinical rounds and nursing care elements in all admissions due to non-COVID-19 pneumonia and ST elevation myocardial infarction during the lockdown period with similar admissions in a baseline period in the same weeks in the previous pre-lockdown. Main outcome measures: To evaluates the changes occurring during the COVID-19 pandemic in terms of the standard care elements, such as the physician rounds and nursing care. Sample size: Total of 113 patients records were analyzed. Results: During the lock down period, a total of 113 patients were admitted to the medical and cardiology wards, (95 patients with pneumonia and 18 patients with ST segment elevation myocardial infarction (STEMI)) compared to 89 patients in the pre lockdown period (74 patients with pneumonia and 15 patients with STEMI). Both groups were similar in age, gender, disposition, length of stay, goal of care planning and outcome. Chronic respiratory disease and Diabetes were more present in patients admitted on the pre lockdown time. Azithromycin was more frequently used as part of the initial antibiotic regimen for pneumonia during the pre-lockdown while doxycycline was significantly more during the lockdown.For the 95 patients admitted in the medical wards during the lockdown, there were a total of 820 physicians' clinical rounds opportunities for senior and junior physicians each. The residents missed 133 (16.2%) and consultant missed 252 (30.7%) of those clinical rounds opportunities. Missed clinical rounds opportunities during the pre-lock down period was higher for residents and consultants at 19.3% (P = 0.429 ) and 36.3% respectively (P = 0.027 ). Similarly, missed clinical rounds opportunities was less during the lockdown period from 35.2% to 25% (p 0.022) and from 38.8% to 30.6% (p = 1 ) for junior staff and consultant cardiology respectively compared to pre lockdown period. For nursing care elements, there was a decrease in missed opportunities in vital signs measurement (p 0.47 and p 0.226), pain assessment (p 0.088 and p 0,366) and skin care (p 0.249 and p 0.576) for patients admitted during the lockdown period in medical and cardiology wards. Conclusions: Caring for patients admitted for non COVID 19 infection reasons, physicians' clinical rounds did marginally increase compared to pre lockdown period while nurses monitoring for those patients was significantly higher. No difference in mortality was observed for patients admitted pre and during lockdown. The number of missed opportunities to do clinical rounds by physicians remains high during both periods and measures to improve adherence of physicians to performed clinical rounds are needed.